Gold nanostar‐based complexes applied for cancer theranostics. Issue 3 (5th January 2022) - Yang, Rui; Gao, Yue; Ouyang, Zhijun; Shi, Xiangyang; Shen, Mingwu
Abstract: Cancer remains a major health problem that plagues human beings, calling widespread attention to develop novel theranostics to achieve sensitive diagnosis and efficient therapy. Multifunctional nanomedicine that can integrate diagnosis with treatment formulations has been emerging as a powerful strategy to overcome the current drawbacks in conventional clinical cancer treatments. Due to the good biocompatibility, easy surface modification, surface‐enhanced Raman spectroscopy (SERS)/computed tomography (CT)/photoacoustic (PA) imaging properties, and exceptional photothermal performance of gold nanostars (AuNSs), various AuNS‐based complexes or nanohybrids including metal compound/AuNSs, SiO2 /AuNSs, polymer/AuNSs, and dendrimer/AuNSs, and so forth have been developed, holding great blueprint in cancer theranostics. Herein, we concisely review the recent progresses in the intriguing design of AuNS‐based nanoplatforms, and their applications in bioimaging, therapy and imaging‐guided cancer treatment, and clarify the possible future perspectives for the design of AuNS‐facilitated cancer theranostics. Abstract : Gold nanostar (AuNS)‐based complexes have been proven to be promising nanoplatforms for cancer theranostics. Herein, the authors concisely review the recent progresses and the state of art in the synthesis strategies and appilications of various AuNS‐based complexes for imaging‐guided cancer therapy, and clarify the future perspectives in the elegant design of AuNS‐based complexes for improved precision cancer nanomedicine applications.